Evaluation of User Experience in the Game "Night's Reach" Using the Game Experience Method Questionnaire (GEQ) - Sherly Damaiyanti; Andreyan Rizky Baskara; Muhammad Fajrian Noor; Muti'a Maulida (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2025)
Students from Lambung Mangkurat University developed a game called "Game Night's Reach" aimed at introducing and preserving wetland environments. To assess the game's viability for release, it is crucial to test the UI/UX to gauge its efficiency. This involves understanding how well players interact with the game and their over-all user experience. The testing is conducted through distributing questionnaires to collect gameplay experience data from new users. The method used is the Game Experience Questionnaire (GEQ), which measures the efficiency of user experience by evaluating players' feelings and experiences while playing the game, beyond just usability aspects like efficiency, perspective, and dependency. Based on the questionnaire data, a redesign was performed in the first phase to improve the game, which will be compared in the second phase. The usability evaluation of "Game Night's Reach" using the GEQ method showed the following changes after redesign: Competence, Increased by 0.198 from 0.872 to 1.068. Immersion, Increased by 0.196 from 0.853 to 1.051. Flow, Increased by 0.29from 0.742 to 1.032. Tension, Increased by 0.1 from 0.51 to 0.61. Challenge, Increased by 0.13 from 0.588 to 0.718.Negative affect, Decreased by 0.103 from 0.545 to 0.442. Positive affect, Increased by 0.106 from 0.894 to 1.008.Empathy, Increased by 0.235 from 0.723 to 0.958. Negative feelings, Decreased by 0.072 from 0.482 to 0.41. Behavioural involvement, Increased by 0.388 from 0.59 to 0.978. Positive experience, Increased by 0.168 from 0.89to 1.058. Negative experience, Decreased by 0.078 from 0.501 to 0.423. Tiredness, Decreased by 0.01 from 0.505 to 0.495. Returning to reality, Increased by 0.334 from 0.646 to 0.986.